A Customized Local Energy Trading Approach Using a Comprehensive Set of Performance Indices - Smitali Patnaik; Umit Cali; Maciej A. Noras (IEEE Access)
This paper presents a customized local energy trading approach using a comprehensive set of performance indices (i.e. Community Savings, Self-Consumption, Self-Sufficiency, Fairness Index, Individual Household Savings) for evaluation of the trading practices. The simulations performed on historical data sets compared dispatch mechanisms based on Mixed Integer Linear Programming (MILP) and techniques originating from Auction-Based approaches. The intent was to use performance metrics in building Local Energy Market (LEM) trading solutions based on a given set of limited inputs and use them to optimize pricing or trading dispatch to get the best consumer returns. Modeling results indicate that the Auction-Based Model performed better than the MILP methods in terms of all performance indices and had potential to provide participants with higher levels of savings.